Radioligands targeting fibroblast activation protein (FAP) - Lindner, Thomas; Giesel, Frederik L.; Kratochwil, Clemens; Serfling, Sebastian E. (Cancers, 2021)
Targeting fibroblast activation protein (FAP) in cancer-associated fibroblasts (CAFs) has attracted significant attention in nuclear medicine. Since these cells are present in most cancerous tissues and FAP is rarely expressed in healthy tissues, anti-FAP tracers have a potential as pan-tumor agents. Compared to the standard tumor tracer [18F]FDG, these tracers show better tumor-to-background ratios (TBR) in many indications. Unlike [18F]FDG, FAP-targeted tracers do not require exhausting preparations, such as dietary restrictions on the part of the patient, and offer the possibility of radioligand therapy (RLT) in a theragnostic approach. Although a radiolabeled antibody was clinically investigated as early as the 1990s, the breakthrough event for FAP-targeting in nuclear medicine was the introduction and clinical application of the so-called FAPI-tracers in 2018. From then, the development and application of FAP-targeted tracers became hot topics for the radiopharmaceutical and nuclear medicine community, and attracted the interest of pharmaceutical companies. The aim of this review is to provide a comprehensive overview of the development of FAP-targeted radiopharmaceuticals and their application in nuclear medicine.